Recent Developments in Alcoholism 1998
DOI: 10.1007/0-306-47148-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging Functional Consequences of Ethanol in the Central Nervous System

Abstract: Abstract. In recent years, sophisticated methods have been developed to view structure and function within the living brain. Functional imaging methods are used to visualize dynamic chemical processes that are linked to brain activity. Increased neural activity, for example, leads to greater glucose and oxygen consumption and greater regional rates of blood flow to meet elevated energy demands. Mapping these changes provides quantitative visual descriptions of localized changes in brain activity that result fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 102 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…2-DG imaging has been used in the alcohol research field to determine LCGU rates in nonselected rat lines immediately after alcohol administration or consumption, when ethanol is present in the CNS. Several studies have shown that the acute administration of alcohol produces anatomically distinct changes in rates of LCGU that are time, dose, and route of administration-dependent (Lyons et al, 1998;Porrino et al, 1998a,b;Porrino, 1994, 1997;Williams-Hemby et al, 1996).…”
mentioning
confidence: 99%
“…2-DG imaging has been used in the alcohol research field to determine LCGU rates in nonselected rat lines immediately after alcohol administration or consumption, when ethanol is present in the CNS. Several studies have shown that the acute administration of alcohol produces anatomically distinct changes in rates of LCGU that are time, dose, and route of administration-dependent (Lyons et al, 1998;Porrino et al, 1998a,b;Porrino, 1994, 1997;Williams-Hemby et al, 1996).…”
mentioning
confidence: 99%
“…Some investigators have found up to 23% reductions in cerebral glucose metabolism after alcohol (Volkow et al, 2005;Wang et al, 2000), whereas others reported much smaller changes (deWit et al, 1990) or even metabolic increases (Lyons et al, 1998). A moderate dose of alcohol increases blood flow in ventral striatum and in the ascending reticular activating system (Ingvar et al, 1998).…”
mentioning
confidence: 99%